Cuerpo-territorio : Estética del aparecer - Librandi, Nancy Beatriz (2017)
In the course of studies of Visual Arts, some subjects approach the representation of the human body according to cannons already established on the basis of a homogenizing academic narrative, the illusion of anatomic accuracy and mimetic realism. This essay attempts to reexamine the body as poetic material in teaching and production contexts. Instead of being objectively represented or presented, we propose building it up in its own appearing, making it believable, credible, possible in the context of its own work, rather than comparing it with an external reality.